2015
DOI: 10.1099/mic.0.000158
|View full text |Cite
|
Sign up to set email alerts
|

Calcium is required for ixotrophy of Aureispira sp. CCB-QB1

Abstract: Ixotrophy is a process that enables certain microbes to prey on other cells. The ability of cells to aggregate or adhere is thought to be a significant initial step in ixotrophy. The gliding, multicellular filamentous bacterium Aureispira sp. CCB-QB1 belongs to the family Saprospiraceae and preys on bacteria such as Vibrio sp. in seawater. Adhesion and cell aggregation were coincident with preying and were hypothesized to play an important role in the ixotrophy in this bacterium. To test this hypothesis, exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
(43 reference statements)
4
14
0
Order By: Relevance
“…Foam samples from our study contained bacterial OTUs likely capable of producing SAS, as previously demonstrated for Vibrio and Pseudoalteromonas (Dang, et al 2016;Hu, et al 2015). Moreover, Saprospira found in Trichodesmium-associated foam can produce sticky substances such as acidic polysaccharides, which enhance aggregate formation (Furusawa, et al 2015). We further speculate that in the Jade Bay, foam formation could be additionally supported by blooming Phaeocystis sp.…”
Section: The Role Of Particles For Foam-populating Bacteria and Biogesupporting
confidence: 81%
See 1 more Smart Citation
“…Foam samples from our study contained bacterial OTUs likely capable of producing SAS, as previously demonstrated for Vibrio and Pseudoalteromonas (Dang, et al 2016;Hu, et al 2015). Moreover, Saprospira found in Trichodesmium-associated foam can produce sticky substances such as acidic polysaccharides, which enhance aggregate formation (Furusawa, et al 2015). We further speculate that in the Jade Bay, foam formation could be additionally supported by blooming Phaeocystis sp.…”
Section: The Role Of Particles For Foam-populating Bacteria and Biogesupporting
confidence: 81%
“…2015). Moreover, Saprospira found in Trichodesmium -associated foam can produce sticky substances such as acidic polysaccharides, which enhance aggregate formation (Furusawa, et al . 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that members of the Aureispira prey on Vibrio sp. in a process linked with the availability of calcium ions (45) and thus may help to counter an increasing abundance of opportunistic bacteria (46).…”
Section: Discussionmentioning
confidence: 99%
“…These events potentially stimulated secondary consumers such as Aureispira, which only appeared after 60 h (Kruskal-Wallis test, p = 0.01). This predatory taxon can feed on metabolic products or cell debris from other bacteria, fueled by its capacity to adhere to anionic polysaccharides [85]. On PecP, a single MAG affiliated with Catenovulum accounted for the vast majority of differentially abundant transcripts, supporting the predisposition of this taxon towards pectin (see below).…”
Section: Do Algp Pecp and Fl Communities Differ In Functional Diversmentioning
confidence: 89%